APPROBATION OF THE MODEL OF PROFESSIONAL SUBJECTIVITY OF FUTURE LINGUISTS THROUGH THE TECHNOLOGY OF DEVELOPMENT OF CRITICAL THINKING - Шуйншкалиев, Заманбек (Вестник ЗКУ, 2024)
The article deals with the problems of developing critical thinking in the professional training of future teachers of legal disciplines future teachers in the context of implementing educational programs and achieving educational results which are relevant to modern society. Examples of tasks aimed at developing the critical thinking of students and future teachers of the English language are given.